Formulation and Evaluation of Fast Disintegrating Tablets Containing Sertraline Solid Dispersion Using Plantago Ovata - Khatal, Hrishikesh K.; Borkar, Smita P.; Jadhav, Prakash D.; Yadav, Vishal D (Asian Journal of Pharmaceutical Research and Development, 2022)
The aim of the present research is to formulate Sertraline Hydochloride solid dispersion (SRT-SD) fast disintegrating tablets. The speed of onset of action of antidepressant drug is clinically important for several reasons. Fast disintegrating tablets of SRT-SD was formulated by using natural superdisintegrant adopting direct compression method to minimize time of onset of action and also become economic. The study describes formulation of solid dispersion of SRT using HPMC E5 as a carrier and further converting SRT-SD into fast disintegrating tablets utilizing Plantago ovata mucilage as natural superdisintegrant. All tablets formulations were evaluated for various pre and post compression parameters. The F1 batch showed release kinetics closest to Serta® with maximum r2 (0.9991) value was considered to be the optimized batch and showed hardness of 3.10 kg/cm2, disintegration time of 28.00 second and dissolution of 95 % in 12 min. The stability study clearly indicate that optimized batch can increase the disintegrating and dissolution time of SRT and utilized as prominent alternative for the treatment of depression.